The release of biologically hazardous chemical compounds from orthodontic adhesive systems used in Europe and in the USA — an in vitro study - Małkiewicz, K.; Wychowański, P.; Małkiewicz, E.; Olczak-Kowalczyk, D.; Turło, J. (Polimery, 2015)
The study assessed the chemical stability of ConTec LC, Resilence, Light Bond and Transbond XT orthodontic adhesive resins. The subject of the analysis was the release of HEMA (2-hydroxyethylmethacrylate), TEGDMA (triethylene glycol dimethacrylate), EGDMA (ethylene glycol dimethacrylate), UDMA (urethane dimethacrylate) and BPA (bisphenol A) monomers from test sample materials in successive time intervals, using HPLC (high pressure liquid chromatography). The study confirmed the presence of methacrylate monomers and bisphenol A in eluates of the assessed materials regardless of the observation period. The results show that orthodontic adhesive systems polymerized with visible light are chemically unstable, releasing biologically harmful ingredients to the external environment for a long time. Dental materials containing polymer network based on methacrylates require structure modification or elimination of harmful components in order to increase safety of their application.